Urban green spaces: lessons from COVID-19 for future public health crises - Natália Cristina de Oliveira; Giovanni Sanesi; Teresa Cristina Brazil de Paiva; Débora Souza Alvim; Danúbia Caporusso Bargos; Caio Fernando Fontana; Sidnei Aranha; Raffaele Lafortezza; Maurício Lamano Ferreira (Environmental Research, 2026)

Landscapes heavily impacted by human activities amplify climate sensitivity of Aleppo pine growth - Onofrio Cappelluti; Giuseppe Colangelo; Vincenzo Giannico; Raffaele Lafortezza; Giovanni Sanesi; Paolo Cherubini; Mario Elia (Agricultural and Forest Meteorology, 2026)

Vertical complexity matters: How canopy height and architecture mitigate urban heat in high-density environments - Hongling Yi; Fei Feng; Xianwen Li; Chengyang Xu; Yongxian Su; Peng Yao; Raffaele Lafortezza (Urban Forestry & Urban Greening, 2026)

Scenario-based simulation of ecosystem service supply and demand in China's Yangtze River Economic Belt - Lanqing Zhang; Fei Feng; Huihui Huang; Yuan Cao; Simin Jiang; Wenlei Shi; Haoyuan Lv; Chenyang Xu; Giovanni Sanesi; Raffaele Lafortezza (Environmental Research, 2025)

Drone-based assessment of urban green space structure and cooling capacity - Na Shen; Fei Feng; Chengyang Xu; Xianwen Li; Maria Vincenza Chiriacò; Raffaele Lafortezza (Urban Forestry & Urban Greening, 2025)

Unravelling the 3D thermal environment differences between forest center and edge: A case study on 22 urban forests in Hefei city, China - Qingqing Ma; Yongxian Su; Xiuzhi Chen; Xiu Meng; Fengyu Zhang; Raffaele Lafortezza; Yiyong Li (Agricultural and Forest Meteorology, 2025)

Understanding the coupling effect of multiple urban features on land surface temperature in Europe - Yaxue Ren; Fei Feng; Mario Elia; Vincenzo Giannico; Giovanni Sanesi; Raffaele Lafortezza (Urban Forestry & Urban Greening, 2025)

Spatiotemporal characteristics and robustness analysis of the thermal network in Beijing, China - Xiang Cao; Fei Feng; Chengyang Xu; Xiaoting Li; Baoquan Jia; Lanqing Zhang; Qiang Yu; Raffaele Lafortezza (Sustainable Cities and Society, 2025)

Assessing the impact of vegetation cover changes and post-fire effects through an enhanced sediment flow connectivity index (SfCI) - Marina Zingaro; Giovanni Scicchitano; Alberto Refice; Antonella Marsico; Alok Kushabaha; Mario Elia; Raffaele Lafortezza; Domenico Capolongo (CATENA, 2024)

Exploring the non-linear impacts of urban features on land surface temperature using explainable artificial intelligence - Fei Feng; Yaxue Ren; Chengyang Xu; Baoquan Jia; Shengbiao Wu; Raffaele Lafortezza (Urban Climate, 2024)

Differentiated influences of atmospheric dryness on urban plant cooling effect between temperate and tropical/subtropical zones - Wenting Yan; Yongxian Su; Jing Zhang; Chaoqun Zhang; Liyang Liu; Xiaodong Liu; Raffaele Lafortezza (Urban Climate, 2024)

Ecological transformation is the key to improve ecosystem health for resource-exhausted cities: A case study in China based on future development scenarios - Simin Jiang; Fei Feng; Xinna Zhang; Chengyang Xu; Baoquan Jia; Raffaele Lafortezza (Science of The Total Environment, 2024)

Satellite observations reveal a decreasing albedo trend of global cities over the past 35 years - Shengbiao Wu; Xingwen Lin; Zunjian Bian; Mathew Lipson; Raffaele Lafortezza; Qiang Liu; Sue Grimmond; Erik Velasco; Andreas Christen; Valéry Masson; Ben Crawford; Helen Claire Ward; et al. (Remote Sensing of Environment, 2024)

Coupling heat wave and wildfire occurrence across multiple ecoregions within a Eurasia longitudinal gradient - Elia Mario; Lafortezza Raffaele; Cappelluti Onofrio; Costa-Saura Josè Maria; Bacciu Valentina; Giannico Vincenzo; Changliang Shao; Sanesi Giovanni (Science of The Total Environment, 2024)

The unrelenting global expansion of the urban heat island over the last century - Yaxue Ren; Raffaele Lafortezza; Vincenzo Giannico; Giovanni Sanesi; Xinna Zhang; Chengyang Xu (Science of The Total Environment, 2023)

Pandemic urban development is leading us away from nature - Raffaele Lafortezza; Clive Davies (Environmental Research, 2023)

Developing Custom Fire Behavior Fuel Models for Mediterranean Wildland–Urban Interfaces in Southern Italy - Mario Elia; Raffaele Lafortezza; Raffaella Lovreglio; Giovanni Sanesi (Environmental Management, 2015)

Assessing the impacts of fragmentation on plant communities in New Zealand: scaling from survey plots to landscapes - Raffaele Lafortezza; David A. Coomes; Valerie Kapos; Robert M. Ewers (Global Ecology and Biogeography, 2010)
Aim Few studies have attempted to assess the overall impact of fragmentation at the landscape scale. We quantify the impacts of fragmentation on plant diversity by assessing patterns of community composition in relation to a range of fragmentation measures. Location The investigation was undertaken in two regions of New Zealand – a relatively unfragmented area of lowland rain forest in south Westland and a highly fragmented montane forest on the eastern slopes of the Southern Alps. Methods We calculated an index of community similarity (Bray–Curtis) between forest plots we regarded as potentially affected by fragmentation and control forest plots located deep inside continuous forest areas. Using a multiple nonlinear regression technique that incorporates spatial autocorrelation effects, we analysed plant community composition in relation to measures of fragmentation at the patch and landscape levels. From the resulting regression equation, we predicted community composition for every forest pixel on land‐cover maps of the study areas and used these maps to calculate a landscape‐level estimate of compositional change, which we term ‘BioFrag’. BioFrag has a value of one if fragmentation has no detectable effect on communities within a landscape, and tends towards zero if fragmentation has a strong effect. Results We detected a weak, but significant, impact of fragmentation metrics operating at both the patch and landscape levels. Observed values of BioFrag ranged from 0.68 to 0.90, suggesting that patterns of fragmentation have medium to weak impacts on forest plant communities in New Zealand. BioFrag values varied in meaningful ways among landscapes and between the ground‐cover and tree and shrub communities. Main conclusions BioFrag advances methods that describe spatial patterns of forest cover by incorporating the exact spatial patterns of observed species responses to fragmentation operating at multiple spatial scales. BioFrag can be applied to any landscape and ecological community across the globe and represents a significant step towards developing a biologically relevant, landscape‐scale index of habitat fragmentation.

Diversity–invasibility relationships across multiple scales in disturbed forest understoreys - Andrew J. Tanentzap; Dawn R. Bazely; Raffaele Lafortezza (Biological Invasions, 2010)

Assessing the current status of urban forest resources in the context of Parco Nord, Milan, Italy - Giovanni Sanesi; Raffaele Lafortezza; Pasquale A. Marziliano; Alessandro Ragazzi; Luigi Mariani (Landscape and Ecological Engineering, 2007)

Sensitivity of landscape measurements to changing grain size for fine-scale design and management - Robert C. Corry; Raffaele Lafortezza (Landscape and Ecological Engineering, 2007)